Bath Salts: A Newly Recognized Cause of Acute Kidney Injury. (21st November 2012) - McNeely, Jonathan; Parikh, Samir; Valentine, Christopher; Haddad, Nabil; Shidham, Ganesh; Rovin, Brad; Hebert, Lee; Agarwal, Anil
Abstract : Bath salts are substance of abuse that are becoming more common and are difficult to recognize due to negative toxicology screening. Acute kidney injury due to bath salt use has not previously been described. We present the case of a previously healthy male who developed acute kidney injury and dialysis dependence after bath salt ingestion and insufflation. This was self-reported with negative toxicology screening. Clinical course was marked by severe hyperthermia, hyperkalemia, rhabdomyolysis, disseminated intravascular coagulation, oliguria, and sepsis. We discuss signs and symptoms, differential diagnoses, potential mechanisms of injury, management, and review of the literature related to bath salt toxicity.